What leads to coordinated attention in parent–toddler interactions? Children's hearing status matters. Issue 3 (22nd November 2019) - Chen, Chi‐hsin; Castellanos, Irina; Yu, Chen; Houston, Derek M.
Abstract: Coordinated attention between children and their parents plays an important role in their social, language, and cognitive development. The current study used head‐mounted eye‐trackers to investigate the effects of children's prelingual hearing loss on how they achieve coordinated attention with their hearing parents during free‐flowing object play. We found that toddlers with hearing loss (age: 24–37 months) had similar overall gaze patterns (e.g., gaze length and proportion of face looking) as their normal‐hearing peers. In addition, children's hearing status did not affect how likely parents and children attended to the same object at the same time during play. However, when following parents' attention, children with hearing loss used both parents' gaze directions and hand actions as cues, whereas children with normal hearing mainly relied on parents' hand actions. The diversity of pathways leading to coordinated attention suggests the flexibility and robustness of developing systems in using multiple pathways to achieve the same functional end. Abstract : The current study used head‐mounted eye‐trackers to investigate the effects of toddlers' prelingual hearing loss on how they achieve coordinated attention with their hearing parents during free‐flowing object play. We found that children's hearing status did not affect how likely parents and children attended to the same object at the same time during play. However, when following parents' attention, children with hearing loss used both parents' gaze directions and hand actions as cues, while children with normal hearing mainly relied on parents' hand actions.